2015
DOI: 10.1038/jcbfm.2015.134
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin-1β Transfer across the Blood–Brain Barrier in the Ovine Fetus

Abstract: Pro-inflammatory cytokines contribute to hypoxic-ischemic brain injury. Blood-brain barrier (BBB) dysfunction represents an important component of hypoxic-ischemic brain injury in the fetus. Hypoxic-ischemic injury could accentuate systemic cytokine transfer across the fetal BBB. There has been considerable conjecture suggesting that systemic cytokines could cross the BBB during the perinatal period. Nonetheless, evidence to support this contention is sparse. We hypothesized that ischemia-reperfusion increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…We have previously shown direct linear correlations between integrated optical density (IOD) values normalized to the IC samples and those normalized to β-actin, when one age group was studied, e.g., newborn lambs [38]. In addition, we have compared claudin-3 expression normalized as the ratio to the IC standard with values normalized as ratios to vinculin and found that the values demonstrated an excellent correlation [31]. Therefore, experimental autoradiographic values are expressed as IOD ratios to the IC samples in order to normalize comparisons between the different groups and immunoblots.…”
Section: Western Immunoblotmentioning
confidence: 95%
See 3 more Smart Citations
“…We have previously shown direct linear correlations between integrated optical density (IOD) values normalized to the IC samples and those normalized to β-actin, when one age group was studied, e.g., newborn lambs [38]. In addition, we have compared claudin-3 expression normalized as the ratio to the IC standard with values normalized as ratios to vinculin and found that the values demonstrated an excellent correlation [31]. Therefore, experimental autoradiographic values are expressed as IOD ratios to the IC samples in order to normalize comparisons between the different groups and immunoblots.…”
Section: Western Immunoblotmentioning
confidence: 95%
“…We examined the cerebral cortex as it represents an important brain region, and because we had residual frozen frontal cerebral cortical samples from our previous studies [4,[29][30][31]. We have recently published a detailed schematic that we have used for our brain sample preparation in similar studies [32].…”
Section: Animal Preparation Study Groups and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The study results of Ma Z et al [9] showed that umbilical cord blood mononuclear cell transplantation combined with hyperbaric oxygen therapy could reduce the expression of IL-1β and TNF-α protein, improve the long-term behavioral ability of hypoxic ischemic neonatal rats and alleviate brain damage. In Sadowska's study, [10] proinflammatory cytokines are involved in inflammatory reaction of hypoxic-ischemic brain damage, and blood brain barrier dysfunction is an important part of fetal hypoxicischemic brain damage. In this case, IL-1β passed through the intact fetal blood-brain barrier, and ischemia/reperfusion also enhanced the possibility of cytokines entering into the blood-brain barrier, resulting in brain injury.…”
Section: The Characteristics Of Hie In Perinatal Neonatesmentioning
confidence: 99%